Complexions and grain growth retardation: First-principles modeling of phase boundaries in WC-Co cemented carbides at elevated temperatures. (1st September 2021) - Fransson, Erik; Gren, Martin; Wahnström, Göran
Graphical abstract: Abstract: WC-Co cemented carbides combine superb hardness with high toughness making them ideal for usage in metal machining and in wear resistant tools. Controlling the WC grain size is important during sintering as grain size plays a crucial role for the mechanical properties of the material. Experimental studies have observed different growth rates and grain morphologies in W-rich and C-rich materials, but the mechanism behind this has not been clarified. Here, we consider the possibility of an interface-stabilized state, a complexion, at the WC/Co phase boundary in cemented carbides, namely thin WC films with cubic structure. An interfacial phase diagram is derived using ab-initio calculations and first-principles modeling. Cluster expansions are employed to model carbon vacancies and Monte Carlo simulations to sample the configurational entropy. Force-constant fitting is used to extract the harmonic free energy for ground-state structures and the effects from anharmonicity and electronic excitations are effectively incorporated from a companion study on WC bulk phases. We predict the stabilization of thin cubic WC films at liquid phase sintering temperatures but only at W-rich conditions. This is consistent with experimental findings where thin films with cubic stacking have been observed predominantly in W-rich materials. We use this knowledge to suggest an explanation for the observed different growth rates and grain morphologies in W-rich and C-rich cemented carbides.